Comparison Of The Effectiveness Of Green Betel Leaf (Piper Betle L) And Red Betel Leaf (Piper Crocatum) Decoction Water Against Pseudomonas Aeruginosa Bacteria, One Of The Causes Of Vaginal Discharge In Vitro - Lumempow, Nurlian J; Ahmad, Mardiana; Sartini, Sartini; Usman, Andi Nilawati; Stang, Stang; Idrus, Hasta Handayani (Journal of Neonatal Surgery, 2025)
Background: Pseudomonas aeruginosa is one of the bacteria associated with vaginal discharge, and the exploration of natural antibacterial agents remains important, especially given rising antibiotic resistance. Betel leaves, both red (Piper crocatum) and green (Piper betle L), have been traditionally used for their antimicrobial properties. Objective: To compare the effectiveness of green and red betel leaf decoction water in inhibiting the growth of Pseudomonas aeruginosa using in vitro methods. Methods: This study employed the microdilution method to determine the Minimum Inhibitory Concentration (MIC) at various concentrations (1%, 0.5%, 0.25%, and 0.125%). Additionally, the agar diffusion method was used to assess the diameter of the inhibition zones produced by both types of betel leaf decoction against Pseudomonas aeruginosa. Results: The red betel leaf decoction showed no inhibitory activity at any tested concentration across all replicates, indicating no detectable MIC. In contrast, the green betel leaf decoction demonstrated inhibitory effects in the first and third replicates at 1% concentration, although bacterial growth persisted in the second replicate and at lower concentrations across all replicates. Agar diffusion results revealed the presence of inhibition zones in green betel leaf decoction at 1% concentration in all replicates, while red betel leaf showed none under similar conditions. Conclusion: Green betel leaf decoction water exhibits greater antibacterial effectiveness against Pseudomonas aeruginosa compared to red betel leaf, particularly at higher concentrations, and may serve as a potential natural alternative in managing vaginal infections. Keywords: Green Betel Leaf (Piper Betle L), Red Betel Leaf (Piper Crocatum), Pseudomonas aeruginosa bacteria, leucorrhoea in vitro.